1999
DOI: 10.1152/ajpendo.1999.276.4.e728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calorie restriction on in vivo glucose metabolism by individual tissues in rats

Abstract: We evaluated the effects of 8 mo of calorie restriction [CR: 60% of ad libitum (AL) food intake] on glucose uptake by 14 tissues in unanesthetized, adult (12 mo) F344×BN rats. Glucose metabolism was assessed by the 2-[3H]deoxyglucose tracer technique at 1500 or 2100. Despite an ∼60% decline in insulinemia with CR, plasma 2-[3H]deoxyglucose clearance for CR was greater than for AL at both times. A small, CR-related decrease in glucose metabolic index ([Formula: see text]) occurred only at 1500 in the spleen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
40
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 31 publications
12
40
0
3
Order By: Relevance
“…In support of this finding, an in vivo study of 12-month-old male rats showed that WAT exhibited greater glucose metabolic indices. Glucose utilization in the preprandial phase, when blood glucose and insulin are low, as well as in the postprandial phase (blood glucose and insulin are high), was greater in CR rats compared with AL-fed rats (Wetter et al 1999). Moreover, the glucose metabolic index did not differ significantly between the pre-and post-prandial phases in CR rats; a finding that supports the insulin independency of glucose uptake in WAT of CR rats.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In support of this finding, an in vivo study of 12-month-old male rats showed that WAT exhibited greater glucose metabolic indices. Glucose utilization in the preprandial phase, when blood glucose and insulin are low, as well as in the postprandial phase (blood glucose and insulin are high), was greater in CR rats compared with AL-fed rats (Wetter et al 1999). Moreover, the glucose metabolic index did not differ significantly between the pre-and post-prandial phases in CR rats; a finding that supports the insulin independency of glucose uptake in WAT of CR rats.…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, adipose tissue-specific overexpression of Glut4 reverses insulin resistance and diabetes in muscle-specific Glut4 knockout mice (Carvalho et al 2005). An in vivo study has indicated that postprandial glucose uptake in WAT is greater in CR rats than in control ad libitum (AL) rats (Wetter et al 1999). Therefore, in the present study, we addressed the issue of whether WAT is involved in glucose-insulin homeostasis modulated by CR.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Possible effects of lipid-deprived diet on the hexosamine biosynthetic pathway Another observation that might be relevant to explain our data is the fact that in certain tissues insulin-stimulated glucose uptake by cells increases in calorie-restricted animals (Wetter et al, 1999 and references therein). Indeed, if this is true for MECs, it would be compatible with higher lactose in the milk of lipid-deprived rats.…”
Section: Discussionmentioning
confidence: 80%
“…In mammals, it is shown that a low phosphate diet alters glucose metabolism [5] [6] and the expression of insulin-sensitive genes [7] [8]. In addition, it is shown that phosphate increases oxidative stress such as Klotho deficiency in mice, causing phosphate retention and impairment of cognition due to increased oxidative damage and apoptosis in Hippocampus neurons [9].…”
Section: Introductionmentioning
confidence: 99%